HUBUNGAN ANTARA SIKAP REMAJA DAN PERAN GURU BIMBINGAN KONSELING DENGAN UPAYA TINDAKAN PREVENTIF HIV/AIDS PADA REMAJA - Novia Luthviatin; Dewi Rokhmah; Syahvira Septyanarindri (Fakultas Kesehatan Masyarakat, Universitas Jember, 2012)
This research objectives are to identify and analyze the relationship between attitudes and the role of guidance counseling teacher with effort of preventing HIV/AIDS in adolescents. The research design is analytical and based on the time of the survey used a cross sectional approach. The number of samples used is 88 samples taken by proportional stratified random sampling technique. Sampling of this research with questionnaires and documentation techniques. Data were analyzed by using Spearman Rank test statistics with 5% signification level. The results showed that there was a significant relationship between the attitude of HIV/AIDS prevention efforts in adolescents with HIV/AIDS in adolescents with p value = 0.029. There was also a significant relationship between the counseling teacher's role with the preventive efforts of HIV/AIDS in adolescents with p value = 0.042. Based on these results, it is expected that the guidance and counseling teachers' to enhance their roles in guiding the teenagers in particular to form a social behavior of adolescents in order to avoid various problems that may result in the association teens today. Keywords : Attitude, Counseling Teacher’s Role, Effort of Preventing HIV/AIDS in Adolescents